Stimulatory effect of engineered three-layer adipose tissue-derived stem cells sheet in atelocollagen matrix on wound healing in a mouse model of radiation-induced skin injury. (October 2019) - Zhang, Yuanzheng; Li, Dan; Fang, Shuo; Li, Xueyang; Zhang, Huojun; Dai, Haiying; Fan, Hao; Li, Yingli; Shen, Di; Tang, Weiya; Yang, Chao; Xing, Xin
To investigate the effectiveness of adipose tissue-derived stem cells sheet combined with atelocollagen matrix on a mouse model of radiation-induced skin injury, adipose tissue-derived stem cells were harvested from the bilateral groin of mice and were screened out by fluorescence-activated cell sorting. Cell sheets were created on a temperature-responsive cell culture surface. The wound recovery rate was detected by measuring the injury area and the recovery shapes of wound were monitored by hematoxylin–eosin, Masson's trichrome, and immunohistochemical staining. Quantitative reverse transcription polymerase chain reaction and Western blot analysis were conducted to detect relative mRNA expression level of interleukin-1β and protein expression level of vascular endothelial growth factor, respectively. As results, the three-layer adipose tissue-derived stem cells sheet combined with atelocollagen matrix treatment promoted wound healing significantly compared to other treatments. More collagen, higher vessel density, and milder inflammation were observed in the group of three-layer adipose tissue-derived stem cells sheet combined with atelocollagen matrix compared with other treatments. Moreover, both mRNA expression level of interleukin-1β and protein expression level of vascular endothelial growth factor were drastically decreased in that group. In conclusion, three-layer adipose tissue-derived stem cells sheet combined with atelocollagen matrix could promote wound healing synergistically, providing a substantial advance in cell-based tissue engineering and wound healing.